2008
DOI: 10.1016/j.ultramic.2008.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of defects on BN nano-structures using high-resolution electron microscopy and density-functional calculations

Abstract: Cubic boron nitride (c-BN) nucleation takes place on hexagonal boron nitride (h-BN) layers growing perpendicular to the substrate surface during thin film synthesis. Studies focused on the nucleation of the cubic phase suggest the possibility that transient phases and/or defects on these h-BN structures have a role in sp3-bonded cubic phase nucleation. In this study, we have investigated the nature, energetics, and structure of several possible defects on BN basal planes, including point defects, 4-, and 5-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The transmission electron microscopy (TEM) image in Figure a shows the sheetlike nanostructure of the as-prepared BN with wrinkles in the center, making it easier to distinguish the presence of sheets and the typical layered compound. The high-resolution TEM image in Figure b displays the interlayer (002) lattice fringe (0.35 nm) of layered BN, which is consistent with the previous reports. , The appearance of some arches (green arrows) and amorphous areas (red circles) demonstrates the existence of some disorders due to the defects and impurities …”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The transmission electron microscopy (TEM) image in Figure a shows the sheetlike nanostructure of the as-prepared BN with wrinkles in the center, making it easier to distinguish the presence of sheets and the typical layered compound. The high-resolution TEM image in Figure b displays the interlayer (002) lattice fringe (0.35 nm) of layered BN, which is consistent with the previous reports. , The appearance of some arches (green arrows) and amorphous areas (red circles) demonstrates the existence of some disorders due to the defects and impurities …”
Section: Results and Discussionsupporting
confidence: 89%
“…18,25 The appearance of some arches (green arrows) and amorphous areas (red circles) demonstrates the existence of some disorders due to the defects and impurities. 26 The X-ray diffraction (XRD) profile of the BNNSs is shown Figure S2 of the Supporting Information. All the peaks can be assigned to those of h-BN (JCPDS Card 45-0896), which strongly agree with those described in the literature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is well known that capping of CNTs require the presence of non-hexagonal carbon rings following Euler's Law, especially pentagonal ones. In our earlier study dealing with the nano-arch geometry in BN structures, we found that nucle-ation of non-hexagonal rings lead to the formation of highly strained non-planar geometries [36]. Motivated with this, we have investigated several non-hexagonal defect structures and their interaction with sulfur atoms in a planar graphene layer.…”
Section: Resultsmentioning
confidence: 95%
“…At the same time, very little information relevant to defect production in BN nanostructures under irradiation can be deduced from the experiments on irradiation of bulk hexagonal and cubic BN systems [482][483][484] or thin BN films. 485 Nevertheless, although the data on the response of these nanomaterials to different kinds of irradiation are quite fragmented, in this section, we try to analyze the available experimental and theoretical results and make conclusions on the general behavior of BN nanosystems under impacts of energetic particles.…”
Section: Boronmentioning
confidence: 99%